Ethical values of individuals at different levels in the organizational hierarchy of a single firm - Harris, James R. (Journal of business ethics, 1990)
This study examines the ethical values of respondents by level in the organizational hierarchy of a single firm. It also explores the possible impacts of gender, education and years of experience on respondents' values as well as their perceptions of how the organization and professional associations influence their personal values. Results showed that, although there were differences in individuals' ethical values by hierarchical level, significantly more differences were observed by the length of tenure with the organization. While respondents, as a whole, were rather ambivalent in their perception of the organization's and professional associations' influence on their values, sales/service persons frequently felt pressured to modify their values in order to achieve company goals.